Strategi Pemasaran dengan menggunakan Analisis SWOT Tanpa Skala Industri Pada PT X Di Jakarta - Arie Wicaksono (Jurnal Manajemen Industri dan Logistik (JMIL), 2017)
In the business competition that increasingly tight along with the development of new technology that more advanced and modern makes Companies attempted to find the quick and appropriate strategy in marketing products to fulfill industry needs. The development of industrial era that gradually grow in the various fields, especially for heavy equipment industry that need to take a strategy in order to win the competition and to obtain larger market share. This research uses quantitative descriptive research method by describing facts and explaining the situation based on facts and figures data that exist and try to analyze the truth through the data obtained. The analytical method used is SWOT Analysis of TSI (No Industry Scale) using EFAS (external factor analysis) and IFAS (internal factor analysis) analysis. The results of this study indicate that company X in using the SWOT Without Industrial Scale puts the strategy of Strength (S)> Opportunity (O), Strategy Opportunity (O)> Weakness (W), Strength Strategy (S)> Threat (T) and Threat Strategy> Weakness (W), so that this condition that PT X is in position to utilize SO strategy which has highest score value that is = 7.6, followed by strategy ST = 6.6, WO = 6.0 and WT=4.8. From these results, the strategy undertaken by company X is to maintain the brand image strategy and penetrate the market to find a larger market share. Strengthening human resources (HR) needs to be done so that companies can add and train human resources, especially professional technicians.